Constructing the Social Image of the Shining Batu Destination Brand : a Study of Tourism Marketing Communication Strategy - Utami, Muherni Asri (Jurnal Spektrum Komunikasi, 2025)
Destination brands in communication science are known as symbols and logos that send messages in the process of reciprocal communication. Destination brands themselves refer to the brand of a destination used to create and promote, by highlighting and enhancing the position and uniqueness of a destination. Destination brands can be used as one of the spearheads of the role to build the positioning of tourist destinations. Then destination brands can also be used to build city identity, distinguishing one city from another. This study uses the Social Construction of Reality theory as an analytical tool; this theory is used to help researchers interpret destination brands. The destination brand studied in this study is Shining Batu, a destination brand from Batu City, East Java. This Social Construction of Reality analogizes a social image of a destination brand that is able to form a reflection of reality. The problem discussed in this study is that destination brands are less understood and known by the public, both the community that owns the destination brand itself and the wider community as the target of tourists at a tourist destination. The purpose of this research is to explore how the existence of a destination brand owned by a tourism destination becomes a source of information and how the existence of a destination brand provides support for tourism marketing communication strategies, so that it can encourage the success of tourism destinations. This research is a post-modern school of thought, using qualitative methodology. This research in data collection uses observation, in-depth interviews and documentation. The conclusion of this study is that the process of constructing a social image of a destination brand as a tourism marketing communication strategy becomes an important part if it is carried out more powerfully by considering all elements of communication.